New technologies and leisure activities for young people in Dakar: small screens connected to the conflicts between parents and teenagers in pikine - Souleymane DIALLO, Dr.; Ousmane BA, Dr. (International Journal of Engineering and Technology, 2022)
The almost irreversible and encouraged link between connectable computer terminals and playful juvenile occupation raises the issue of parental education in the family environment. The latter is characterized by its narrowness and the almost daily absence of parents, hence the question of the uncontrolled use of tablets and smartphones connected by Middle School students from Pikine. Thanks to qualitative methods and semi-structured interviews with fourteen (14) teenagers and their parents, we discover that fathers and mothers are missing from homes on a daily basis because of work. They give to their offspring these devices and the connection not only to occupy them usefully but also to protect them from the evil temptations of the outside. Free, these young people, devote themselves to video games, sports, music, pornography, etc. offered by different websites. Thus, they idealize and copy bad models taken from the net. Conflicts with parents arise. Sanctions follow and the most painful is the withdrawal of the devices.Â Â